ANALISIS MANFAAT DAN COST PENEMPATAN INVESTASI DANA HAJI PADA PEMBANGUNAN INFRASTRUKTUR - Teguh Teguh; Nur Diana (Universitas Islam Malang, 2019)
ABSTRACT This study was conducted to find out the benefits and costs of the placement of Hajj funds in infrastructure development / supply projects based on Islamic / Syari’ah of Indonesian constitution. Employing annual report Hajj Financial Management Agency (BPKH) as the data source was then descriptive qualitative research design used in this study. The results of Hajj finances of this study can be invested to support financing / infrastructure provision, secondly according to the Hajj financial investment law, it is prioritized to increase Hajj services. Therefore, the prospect of pilgrims would experience the benefits totally. Hajj financial funds can be invested to support financing / infrastructure provision because the hajj finance has the deposit nature fund so that it resembles the use of wadiah yadh dhamanah principle in an Islamic / sharia financial perspective thus, as to enable managers (BPKH) to optimize the benefits of hajj funds and prioritize security / integrity of the funds of pilgrims. In this sense, as mentioned in that the Hajj finances in Law 34/2014 are deposit funds (wadiah yadh dhamamah), the implementation of investments in infrastructure financing is limited to the varieties of investments that are very safe and have the certainty of full returns, such as nation of sukuk. Keywords: benefits, cost of HajjfundsandinfrastructureDevelopment